Heavy-intensity priming exercise attenuates the rate of quadriceps muscle fatigue and improves time-to-task failure during severe-intensity cycling - MacDougall, K. B.; Aboodarda, S. J.; Wickenberg, A. B.; Macintosh, B. R. (Medicine & Science in Sports & Exercise, 2025)
Background Prior high-intensity exercise (priming) has been shown to accelerate the oxygen uptake (VO2) kinetics, as well as improve exercise tolerance during subsequent high-intensity exercise, yet the mechanisms underpinning the performance changes are unclear. In theory, a reduced reliance on non-oxidative energy input afforded by the faster VO2 response may improve subsequent performance by delaying muscle fatigue; however, this effect has yet to be conclusively shown.